High-strength flexible polymer tablecloth based on transparent silk effect and preparation method thereof
By using a combination of modified polypropylene matrix material, nanosilica, silicone modifier and nucleating agent in polypropylene materials, the uneven dispersion caused by nanoparticle agglomeration is solved, and the antistatic and mechanical properties of the material are significantly improved, meeting the needs of high-quality home products.
Patent Information
- Application Number
- CN202411688614.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-25
AI Technical Summary
After the addition of nanoparticles in existing polypropylene materials, the nanoparticles are prone to agglomeration, resulting in uneven dispersion, affecting the material performance, especially the antistatic properties.
Using a combination of modified polypropylene matrix material, nanosilica, silicone modifier and nucleating agent, chemical bonds with nanosilica are formed through a silicone modifier to avoid agglomeration, and the crystallization of the material is promoted through a nucleating agent, improving transparency and impact resistance.
The uniform dispersion of nanoparticles is achieved, the anti-static properties, mechanical strength and transparency of the material are improved, and the market demand for high-quality home products is met.
Smart Images

Figure CN119176991B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polypropylene polymer materials, in particular to a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof. Background Art
[0002] In the field of polymer flexible materials, with the diversification of consumer demand and the rapid development of materials science, polymer materials with both high strength and flexibility have been widely used in fields such as home furnishing and decoration. In recent years, polymer materials with high transparency and flexibility have been particularly favored by the market, because such materials not only require good mechanical properties, but also need to be close to the texture of natural silk to meet consumers' dual needs for beauty and function. Polypropylene (PP) materials are widely used in consumer and industrial products due to their excellent mechanical properties, chemical resistance, low density and cost advantages. In order to enhance the antistatic properties and strength of polypropylene materials, nanoparticles (such as silica, nanocellulose, graphene, etc.) are usually added in the prior art to enhance the material properties. However, due to the high specific surface area and small particle size of nanoparticles, they are prone to agglomeration in the matrix, resulting in uneven dispersion and affecting the final material properties. Therefore, how to improve the dispersibility of nanoparticles to avoid electrostatic aggregation while maintaining high transparency and silk texture has become an important technical problem in this field. Summary of the invention
[0003] In the prior art, material properties are usually enhanced by adding nanoparticles (such as silica, nanocellulose, graphene, etc.). However, due to the high specific surface area and small particle size of nanoparticles, they tend to agglomerate in the matrix, resulting in uneven dispersion and affecting the final material properties.
[0004] The present application provides a high-strength flexible polymer tablecloth based on a transparent silk effect. The polymer material used for the tablecloth includes 80 to 90 parts of a modified polypropylene matrix material, 1 to 5 parts of nano-silicon dioxide, 5 to 10 parts of a siloxane modifier, and 0.1 to 0.5 parts of a nucleating agent.
[0005] As a preferred technical solution for a high-strength flexible polymer tablecloth, the polymer material used for the tablecloth includes 85 parts of modified polypropylene matrix material, 2 parts of nano-silicon dioxide, 5 parts of siloxane modifier and 0.4 parts of nucleating agent.
[0006] It should be noted that the modified polypropylene matrix material forms a cross-linked structure through the action of the initiator, which significantly improves the heat resistance and mechanical strength of the material. Nano-silica enhances the tensile strength of the material by dispersing in the matrix. However, since nanoparticles are prone to agglomeration, siloxane modifiers (such as aminosiloxane) play a key role in this process. The polar functional groups in siloxane react with the hydroxyl groups on the surface of silica to form a good chemical bond, avoiding agglomeration. At the same time, a polar coating is formed on the surface of the matrix, which effectively captures and disperses static charges, significantly improving the antistatic performance. The addition of nucleating agents (such as 3,4-dimethyldibenzyl sorbitol) promotes the crystallization of the matrix, making the microstructure of the material more delicate, and further improving the transparency and impact resistance. The synergistic effect of these components makes the polymer tablecloth have both good mechanical properties and antistatic properties, meeting the market demand for high-quality home products.
[0007] As a preferred technical solution for a high-strength flexible polymer tablecloth, the siloxane modifier is aminosiloxane.
[0008] It should be noted that, on the one hand, siloxane molecules usually contain reactive functional groups at their ends, such as amino groups (-NH 2 ), hydroxyl (-OH) or alkyl, etc. These functional groups can react chemically with the hydroxyl groups on the surface of nano-silica or form hydrogen bonds, so that the chemical structure of aminosiloxane enables it to form a good chemical bond with the surface of nano-silica. The siloxane segments in siloxane match the hydrophobicity of polypropylene, thereby enhancing the interfacial compatibility between the filler and the polypropylene matrix. This enhanced compatibility effectively reduces the interfacial energy, promotes the uniform dispersion of nano-silica, and avoids the agglomeration of fillers in the polypropylene matrix. On the other hand, aminosiloxane molecules contain amino groups (–NH 2 ) and other polar functional groups. The amino group is hydrophilic and can adsorb water molecules in the air, increasing the conductivity of the material surface. The presence of water reduces the resistivity of the polypropylene surface, making it easier to discharge static charges, thereby improving the antistatic performance.
[0009] As a preferred technical solution for a high-strength flexible polymer tablecloth, the nucleating agent is 3,4-dimethyldibenzyl sorbitol.
[0010] It should be noted that the nucleating agent can form uniform microscopic crystal nuclei in the modified polypropylene matrix, significantly accelerating the crystallization process of polypropylene.
[0011] In addition, the present invention provides a method for preparing a high-strength flexible polymer tablecloth, comprising the following steps:
[0012] Add the modified polypropylene matrix material into the reactor, heat it at 180°C to 230°C in advance, add aminosiloxane into the reactor, stir for 30 minutes, finally, add nano silicon dioxide into the reactor, disperse it with a high-speed stirrer, and then add 3,4-dimethyldibenzyl sorbitol into the reactor;
[0013] Pour the evenly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 180°C to 230°C, the pressure is 20 to 30 MPa, and the speed is 1 to 3 m / min.
[0014] It should be noted that, first, the modified polypropylene matrix material is heated to 180°C to 230°C, which improves the fluidity of the matrix material and facilitates the dispersion and combination of subsequent added substances. After the aminosiloxane is added, the polar functional groups in the siloxane modifier form chemical or hydrogen bond interactions with the polypropylene matrix and nano-silica by stirring for 30 minutes, thereby improving the interface compatibility between the components and enhancing the mechanical strength and antistatic properties of the material.
[0015] Next, the addition of nano-silica plays a role of filling and strengthening. Through high-speed stirring and dispersion, the nano-silica particles are evenly distributed in the polypropylene matrix, avoiding agglomeration and improving heat resistance and strength. 3,4-Dimethyldibenzyl sorbitol as a nucleating agent promotes crystallization and generates fine crystal nuclei, further improving the mechanical properties and transparency of the material. Finally, in the calendering process, the material is pressed into a 0.5 mm to 1 mm thick film structure at a temperature of 180°C to 230°C, a pressure of 20 to 30 MPa and an appropriate speed.
[0016] As a preferred technical solution for the preparation method of a high-strength flexible polymer tablecloth, the preparation method of the modified polypropylene matrix material comprises:
[0017] The polypropylene resin, dibenzophenone disulfide and initiator are accurately weighed according to the set ratio, the weighed raw materials are added to a high-speed mixer, and stirred at room temperature for 5 minutes to 10 minutes to form a premix, and the premix is fed into a twin-screw extruder. The temperature settings of the extruder should be 170°C, 180°C, 190°C, 200°C, and 210°C from the feeding section to the die. The molten blend is extruded from the extruder die to form a continuous molten strip. The molten strip is quickly cooled and solidified by a water bath or air cooling. Then, the solidified molten strip is cut into uniform particles using a pelletizer to obtain modified polypropylene pellets.
[0018] It should be noted that, first, polypropylene resin, dithiobenzophenone and initiator are mixed in proportion, and in the extrusion process, the temperature is gradually increased from 170°C to 210°C, so that the polypropylene can fully react with dithiobenzophenone and initiator in the molten state to achieve uniform molecular chain crosslinking. This process makes the polypropylene matrix have a more stable structure after cooling, avoiding internal defects and stress concentration, thereby improving the overall strength and thermal stability of the material. The cooled molten strips are rapidly solidified to ensure the uniform microstructure of the polypropylene, and finally uniform modified polypropylene pellets are obtained after pelletizing. These modified pellets have excellent mechanical properties and thermal stability, providing ideal basic materials for the subsequent preparation of high-strength flexible polymer tablecloths.
[0019] As a preferred technical solution for a method for preparing a high-strength flexible polymer tablecloth, the initiator is dicumyl peroxide.
[0020] It should be noted that as a thermal decomposition initiator, dicumyl peroxide decomposes at a relatively high temperature (170°C to 210°C) to generate free radicals, which can trigger the cross-linking reaction between polypropylene and dibenzophenone disulfide. This cross-linking reaction connects the polypropylene molecular chains by forming chemical bonds, thereby constructing a denser three-dimensional structural network, improving the mechanical strength and heat resistance of the material.
[0021] As a preferred technical solution for a method for preparing a high-strength flexible polymer tablecloth, the mass ratio of polypropylene resin, dibenzophenone disulfide and dicumyl peroxide is 10:(0.1-0.5):(0.03-0.05).
[0022] The high-strength flexible polymer tablecloth of the present application has significant beneficial effects. First, through the innovative design of the modified polypropylene matrix material and the reasonable formula combination, the tablecloth maintains excellent strength and transparency while having high strength. Secondly, the uniform dispersion of nano-silicon dioxide and the use of siloxane modifiers form a polar coating on the surface of the material, which effectively improves the antistatic properties and avoids pollution and inconvenience caused by static electricity accumulation. In addition, the addition of the nucleating agent 3,4-dimethyldibenzyl sorbitol accelerates the crystallization process of the material, significantly improves the transparency and mechanical strength, and presents a silk-like visual effect. Finally, the tablecloth material realizes an efficient preparation process through reasonable process parameter control, ensures the high quality of the finished product, meets the market demand for high-performance flexible decorative materials, and has broad application prospects in the fields of home furnishing and decoration. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0024] Figure 1 Electron micrographs of the polypropylene composition materials prepared in Example 1 and Comparative Example 1, (a) corresponds to Comparative Example 1, and (b) corresponds to Example 1;
[0025] Figure 2 This is the experimental data diagram of Example 5. DETAILED DESCRIPTION
[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0029] Preparation Example 1
[0030] The preparation method of the modified polypropylene matrix material comprises:
[0031] According to the set ratio, 10 parts of polypropylene resin, 0.4 parts of dibenzophenone disulfide and 0.05 parts of diisopropylbenzene peroxide are accurately weighed, and the weighed raw materials are added to a high-speed mixer, stirred at room temperature for 10 minutes to form a premix, and the premix is fed into a twin-screw extruder. The temperature setting of the extruder should be from the feeding section to the head as follows: 170°C (feeding section), 180°C (pre-melting zone), 190°C (melting mixing zone), 200°C (reaction promotion zone), 210°C (homogenizing zone). The molten blend is extruded from the extruder head to form a continuous molten strip. The molten strip is quickly cooled and solidified by a water bath or air cooling. Then, the solidified molten strip is cut into uniform particles using a pelletizer to obtain modified polypropylene pellets.
[0032] Preparation Example 2
[0033] The preparation method of the polypropylene matrix material comprises:
[0034] According to the set ratio, 10.4 parts of polypropylene resin and 0.05 parts of diisopropylbenzene peroxide are accurately weighed, and the weighed raw materials are added to a high-speed mixer. They are stirred at room temperature for 10 minutes to form a premix, and the premix is fed into a twin-screw extruder. The temperature settings of the extruder should be as follows from the feeding section to the die: 170°C (feeding section), 180°C (pre-melting zone), 190°C (melting and mixing zone), 200°C (reaction promotion zone), 210°C (homogenizing zone). The molten blend is extruded from the extruder die to form a continuous molten strip. The molten strip is quickly cooled and solidified by a water bath or air cooling. Then, the solidified molten strip is cut into uniform particles using a pelletizer to obtain polypropylene pellets.
[0035] Example 1
[0036] Example 1 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0037] The polymer material for the tablecloth includes 90 parts of modified polypropylene matrix material (Preparation Example 1), 4 parts of nano silicon dioxide, 10 parts of aminosiloxane and 0.5 parts of 3,4-dimethyldibenzyl sorbitol.
[0038] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0039] 90 parts of modified polypropylene matrix material were added to the reactor, which was preheated at 220°C, and then 10 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 4 parts of nano-silicon dioxide were added to the reactor and dispersed using a high-speed stirrer, and then 0.5 parts of 3,4-dimethyldibenzyl sorbitol were added to the reactor;
[0040] Pour the evenly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 230°C, the pressure is 20 MPa, and the speed is 3 m / min.
[0041] Example 2
[0042] Example 2 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0043] The polymer material for the tablecloth includes 85 parts of modified polypropylene matrix material (Preparation Example 1), 2 parts of nano silicon dioxide, 5 parts of aminosiloxane and 0.4 parts of 3,4-dimethyldibenzyl sorbitol.
[0044] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0045] 85 parts of modified polypropylene matrix material were added to the reactor, which was preheated at 180°C, and then 5 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 2 parts of nano-silicon dioxide were added to the reactor and dispersed using a high-speed stirrer, and then 0.4 parts of 3,4-dimethyldibenzyl sorbitol were added to the reactor;
[0046] Pour the uniformly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 180°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0047] Example 3
[0048] Example 3 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0049] The polymer material for the tablecloth includes 80 parts of modified polypropylene matrix material (Preparation Example 1), 5 parts of nano silicon dioxide, 5 parts of aminosiloxane and 0.1 parts of 3,4-dimethyldibenzyl sorbitol.
[0050] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0051] 80 parts of modified polypropylene matrix material were added to the reactor, which was preheated at 230°C, and then 5 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 5 parts of nano-silicon dioxide were added to the reactor and dispersed using a high-speed stirrer, and then 0.1 parts of 3,4-dimethyldibenzyl sorbitol were added to the reactor;
[0052] Pour the evenly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 200°C, the pressure is 25 MPa, and the speed is 1 m / min.
[0053] Example 4
[0054] Example 4 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0055] The polymer material for the tablecloth includes 85 parts of modified polypropylene matrix material (Preparation Example 1), 1 part of nano silicon dioxide, 8 parts of aminosiloxane and 0.3 parts of 3,4-dimethyldibenzyl sorbitol.
[0056] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0057] 85 parts of modified polypropylene matrix material were added to the reactor, which was preheated at 180°C, and then 8 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 1 part of nano-silicon dioxide was added to the reactor and dispersed using a high-speed stirrer, and then 0.3 parts of 3,4-dimethyldibenzyl sorbitol was added to the reactor;
[0058] Pour the evenly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 220°C, the pressure is 30 MPa, and the speed is 2 m / min.
[0059] Example 5
[0060] Example 5 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0061] The polymer material for the tablecloth includes 85 parts of modified polypropylene matrix material (Preparation Example 1), 5 parts of nano silicon dioxide, aminosiloxane (1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts) and 0.3 parts of 3,4-dimethyldibenzyl sorbitol.
[0062] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0063] 85 parts of modified polypropylene matrix material were added to a reactor, which was preheated at 210°C, and then (1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, and 15 parts) of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 5 parts of nano-silicon dioxide were added to the reactor and dispersed using a high-speed stirrer, and then 0.3 parts of 3,4-dimethyldibenzyl sorbitol were added to the reactor;
[0064] Pour the evenly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 190°C, the pressure is 25 MPa, and the speed is 2 m / min.
[0065] Comparative Example 1
[0066] Comparative Example 1 provides a high-strength flexible polymer tablecloth based on transparent silk effect and a preparation method thereof, wherein:
[0067] The polymer material for the tablecloth includes 90 parts of modified polypropylene matrix material (Preparation Example 1), 2 parts of nano silicon dioxide and 0.4 parts of 3,4-dimethyldibenzyl sorbitol.
[0068] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0069] 90 parts of modified polypropylene matrix material were added into the reaction kettle, which was preheated at 180° C., 2 parts of nano-silicon dioxide were added into the reaction kettle, and dispersed by a high-speed stirrer, and 0.4 parts of 3,4-dimethyldibenzyl sorbitol were added into the reaction kettle;
[0070] Pour the uniformly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 180°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0071] Comparative Example 2
[0072] Comparative Example 2 provides a high-strength flexible polymer tablecloth based on a transparent silk effect and a preparation method thereof, wherein:
[0073] The polymer material for the tablecloth includes 85 parts of a polypropylene matrix material (Preparation Example 2), 2 parts of nano silicon dioxide, 5 parts of aminosiloxane and 0.4 parts of 3,4-dimethyldibenzyl sorbitol.
[0074] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0075] 85 parts of modified polypropylene matrix material were added to the reactor, which was preheated at 180°C, and then 5 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 2 parts of nano-silicon dioxide were added to the reactor and dispersed using a high-speed stirrer, and then 0.4 parts of 3,4-dimethyldibenzyl sorbitol were added to the reactor;
[0076] Pour the uniformly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 180°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0077] Comparative Example 3
[0078] Comparative Example 3 provides a high-strength flexible polymer tablecloth based on transparent silk effect and a preparation method thereof, wherein:
[0079] The polymer material for the tablecloth includes 87 parts of modified polypropylene matrix material (Preparation Example 1), 5 parts of aminosiloxane and 0.4 parts of 3,4-dimethyldibenzyl sorbitol.
[0080] The method for preparing a high-strength flexible polymer tablecloth is characterized by comprising the following steps:
[0081] 87 parts of modified polypropylene matrix material were added to the reaction kettle, which was preheated at 180°C, and then 5 parts of aminosiloxane were added to the reaction kettle, stirred for 30 minutes, and finally, 0.4 parts of 3,4-dimethyldibenzyl sorbitol were added to the reaction kettle;
[0082] Pour the uniformly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 180°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0083] Table 1 shows the composition ratios of the polypropylene compositions of Examples 1 to 5 and Comparative Examples 1 to 3.
[0084] project Modified polypropylene matrix material / part Nano silicon dioxide / part Aminosilicone / part 3,4-Dimethyldibenzyl sorbitol / part Example 1 90 4 10 0.5 Example 2 85 2 5 0.4 Example 3 80 5 5 0.1 Example 4 85 1 8 0.3 Example 5 85 5 1 to 15 0.3 Comparative Example 1 90 2 0 0.4 Comparative Example 2 85 2 5 0.4 Comparative Example 3 87 0 5 0.4
[0085] Performance testing
[0086] 1. According to GB / T 1040.3-2006 standard, use a tensile testing machine to test the tensile strength of the material at room temperature;
[0087] 2. According to GB / T 12703.2-2009 standard, use an electrostatic voltage tester to measure the surface resistance or electrostatic decay time of the material;
[0088] 3. Test the heat deformation temperature (HDT) of polypropylene composite materials according to ASTM D648 standard;
[0089] Table 2 Experimental data of Examples 1 to 4 and Comparative Examples 1 to 3
[0090] project Tensile strength (MPa) Surface resistance (Ω) HDT (℃) Example 1 67.8 <![CDATA[3.15×10 8 ]]> 118 Example 2 74.2 <![CDATA[4.58×10 9 ]]> 121 Example 3 69.5 <![CDATA[7.89×10 9 ]]> 109 Example 4 62.9 <![CDATA[5.46×10 7 ]]> 116 Comparative Example 1 45.6 <![CDATA[5.68×10 13 ]]> 85 Comparative Example 2 48.7 <![CDATA[8.81×10 9 ]]> 76 Comparative Example 3 41.5 <![CDATA[6.35×10 10 ]]> 91
[0091] Combined with Example 1, Comparative Example 1 and Figure 1 It can be seen that the surface of the material prepared in Example 1 is relatively smooth, and the particle distribution is relatively small and uniform, while the surface of the material prepared in Comparative Example 1 is relatively rough, and the particle distribution is uneven. This may be because the siloxane molecules usually contain active functional groups at their ends, such as amino groups (-NH 2), hydroxyl (-OH) or alkyl, etc. These functional groups can react chemically with the hydroxyl groups on the surface of nano-silica or form hydrogen bonds, so that the chemical structure of the base siloxane enables it to form a good chemical bond with the surface of nano-silica. The siloxane segments in the siloxane match the hydrophobicity of polypropylene, thereby enhancing the interfacial compatibility between the filler and the polypropylene matrix. This enhanced compatibility effectively reduces the interfacial energy, promotes the uniform dispersion of nano-silica, and avoids the agglomeration of fillers in the polypropylene matrix.
[0092] Combining Examples 1 to 4 and Table 2, it can be seen that the tensile strength, surface resistance and heat deformation temperature of the polypropylene composition material prepared by the formulation and process of the present application are 62.9 MPa to 74.2 MPa, 5.46×10 7 Ω to 7.89×10 9 Ω and 109℃ to 121℃, the material has excellent mechanical properties, heat resistance and antistatic properties, is suitable for high-quality flexible home products, and meets the market demand for high-strength, transparent flexible materials.
[0093] Combining Example 2, Comparative Example 1 and Table 2, it can be seen that the tensile strength, surface resistance and heat deformation temperature of the polypropylene polymer material prepared in Example 2 are better than those of the polypropylene composite material prepared in Comparative Example 1. On the one hand, when the siloxane modifier is added to the polypropylene composite material, its inorganic silicon oxygen chain segment can form hydrogen bonds or chemical bonds with the surface hydroxyl groups or defect sites of nano-silicon dioxide. This combination not only reduces the tendency of agglomeration between nanoparticles, but also helps to evenly disperse the nanoparticles in the polypropylene matrix, thereby relatively improving the mechanical properties and heat resistance of the polypropylene resin. On the other hand, the aminosiloxane molecule contains amino groups (–NH 2 ) and other polar functional groups. The amino group is hydrophilic and can adsorb water molecules in the air, increasing the conductivity of the material surface. The presence of water reduces the resistivity of the polypropylene surface, making it easier to discharge static charges, thereby improving the antistatic performance.
[0094] Combining Example 2, Comparative Example 2 and Table 2, it can be seen that the tensile strength and heat deformation temperature of the polypropylene polymer material prepared in Example 2 are better than those of the polypropylene composition material prepared in Comparative Example 2. Through the modification of dithiobenzophenone, the polypropylene resin undergoes a free radical-induced crosslinking reaction under the action of high temperature and initiator to form a crosslinked network structure. This structure significantly improves the tensile strength and heat resistance of the material, so that the modified polypropylene has significantly improved mechanical and thermal properties, meeting the requirements for the application of the material under high strength and high temperature conditions.
[0095] Combining Example 2, Comparative Example 3 and Table 2, it can be seen that the tensile strength, surface resistance and heat deformation temperature of the polypropylene polymer material prepared in Example 2 are better than those of the polypropylene composition material prepared in Comparative Example 3, wherein the surface resistance value does not change significantly, the dispersion of nano-silicon dioxide in the polypropylene resin has a significant effect on the tensile strength and heat deformation temperature, and a relatively weak effect on the antistatic performance, a strong interaction is formed between the nano-silicon dioxide and the polymer chain, the interfacial adhesion is enhanced, the movement of the chain segments is restricted, and the mechanical and thermal properties of the material are improved. In contrast, the effect of nano-silicon dioxide on the antistatic performance is relatively weak because it cannot effectively reduce the resistivity of the material and cannot form a conductive path.
[0096] Combined with Example 5 and Figure 2 It can be seen that when the addition amount of aminosilicone is 1 to 5 parts, the surface resistance value slowly decreases from nearly 10 14 Ω is reduced to about 10 12 Ω, the rate of decrease is relatively slow. When the amount of aminosiloxane added is 5 to 10 parts, the surface resistance value drops sharply, from 10 12 Ω is reduced to about 10 8 Ω, when the amount of aminosiloxane added is 10 to 15 parts, the surface resistance value gradually stabilizes at about 10 8 Ω; the concentration of aminosilicone is low, and a thin polar coating is gradually formed on the surface of the material. Since the coating has not completely covered the surface of the material, the capture and dispersion effect of static charge is limited, so the surface resistance value decreases slowly. When the addition amount of aminosilicone reaches 5 to 10 parts, aminosilicone forms a relatively complete polar coating on the surface of the material, and the polar amino groups are evenly distributed on the surface of the material, which greatly improves the capture and dispersion ability of static charge. This coating captures static charge through polarity and quickly disperses it, reduces the local aggregation of static charge, and prevents static electricity accumulation. Therefore, the surface resistance value is greatly reduced at this stage. When the addition amount of aminosilicone exceeds 10 parts, the polar coating on the surface of the material is close to saturation, and the polar groups of the aminosilicone molecular layer have fully covered the surface of the material. Further increasing the amount of aminosilicone has little effect on the regulation effect of charge distribution. Therefore, the surface resistance value decreases slowly and tends to be stable.
[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above examples, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. High-strength flexible polymer tablecloth based on transparent silk effect, characterized in that, The polymer material for the tablecloth comprises 80 to 90 parts of a modified polypropylene matrix material, 1 to 5 parts of nano silicon dioxide, 5 to 10 parts of a siloxane modifier and 0.1 to 0.5 parts of a nucleating agent; The preparation method of the polymer tablecloth comprises the following steps: Add the modified polypropylene matrix material into the reactor, preheat it at 180°C to 230°C, then add the siloxane modifier into the reactor, stir for 30 minutes, finally, add nano-silicon dioxide into the reactor, disperse it with a high-speed stirrer, and then add the nucleating agent into the reactor; Pour the uniformly mixed polypropylene composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for standby use, wherein the temperature of the calender is 180° C. to 230° C., the pressure is 20 to 30 MPa, and the speed is 1 to 3 m / min; The siloxane modifier is aminosiloxane; The nucleating agent is 3,4-dimethyldibenzyl sorbitol; The preparation method of the modified polypropylene matrix material comprises: The polypropylene resin, dibenzophenone disulfide and initiator are accurately weighed according to the set ratio, and the weighed raw materials are added to a high-speed mixer, and stirred at room temperature for 5 minutes to 10 minutes to form a premix, and the premix is fed into a twin-screw extruder. The temperature settings of the extruder should be 170°C, 180°C, 190°C, 200°C, and 210°C from the feeding section to the die head, and the molten blend is extruded from the extruder die head to form a continuous molten strip, and the molten strip is quickly cooled and solidified by a water bath or air cooling, and then the solidified molten strip is cut into uniform particles by a pelletizer to obtain modified polypropylene pellets; The initiator is dicumyl peroxide; The mass ratio of polypropylene resin, dibenzophenone disulfide and diisopropylbenzene peroxide is 10:(0.1-0.5):(0.03-0.05).
2. The high-strength flexible polymer tablecloth according to claim 1, characterized in that: The polymer material used for the tablecloth comprises 85 parts of modified polypropylene matrix material, 2 parts of nano silicon dioxide, 5 parts of siloxane modifier and 0.4 parts of nucleating agent.
Citation Information
Patent Citations
Stress whitening resistant polypropylene composite material and preparation method thereof
CN111607150A
Long-acting melt-blown polypropylene electret master batch, preparation method thereof and melt-blown non-woven fabric
CN112778632A